Keefektifan Strategi TPRC (Think, Predict, Read, Connect) Dalam Pembelajaran Membaca Pemahaman Siswa Kelas X SMA Negeri 1 Tangse: The Effectiveness of TPRC (Think, Predict, Read, Connect) Strategy in Reading Comprehension Learning for Grade X Students of SMA Negeri 1 Tangse - Ikram, Fauzan; Rahmi, Hayatun; Nofiana S (KIRANA : Social Science Journal, 2025)
The study titled "The Effectiveness of the TPRC Strategy in Reading Comprehension Learning at SMA Negeri 1 Tangse" aims to evaluate whether there is a significant difference in reading comprehension skills between students taught using the TPRC strategy and those taught without it, as well as to assess the effectiveness of the TPRC strategy in improving students' reading comprehension skills at SMA Negeri 1 Tangse. This study was conducted on December 24, 2024, during the second semester of the 2024/2025 academic year. The research method used was an experimental design with a control group pretest-posttest design. The study population included all tenth-grade students at SMA Negeri 1 Tangse, totaling 64 students, and the sampling technique was simple random sampling. The instrument used was a multiple-choice reading comprehension skills test. The instrument's content validity was tested, and the instrument’s reliability yielded an alpha value of 0.811 using the Iteman program, indicating a high level of reliability. Data analysis was performed using a t-test at a 5% significance level after meeting the assumptions of normality and homogeneity. The results showed that the t-test on the posttest scores of reading comprehension skills between the control group and the experimental group yielded a th value of 3.163, which is greater than the tt value of 2.00 (3.163 > 2.00), with a p-value of 0.002 (0.002 < 0.05 = significant) and degrees of freedom (df) of 62. This indicates a significant difference in reading comprehension skills between the two groups. The average improvement score in reading comprehension skills in the experimental group was 6.19, while the control group showed only a 2.12-point increase. This study concludes that the TPRC strategy is more effective in improving students’ reading comprehension skills than learning without the TPRC strategy. The researcher recommends that schools integrate the TPRC strategy regularly in reading comprehension classes and develop teacher training on the implementation of this strategy to achieve more optimal learning outcomes.